Effects of rapamycin on cell apoptosis in MCF-7 human breast cancer cells - Wirdatul-Nur, Mohd Khairi; Shaharum, Shamsuddin; Azman, Seeni (2014)
Rapamycin is an effective anti-angiogenic drug. However, the mode of its action remains unclear. Therefore, in this study, we aimed to elucidate the antitumor mechanism of rapamycin, hypothetically via apoptotic promotion, using MCF-7 breast cancer cells. MCF-7 cells were plated at a density of 15105 cells/well in 6-well plates. After 24h, cells were treated with a series of concentrations of rapamycin while only adding DMEM medium with PEG for the control regiment and grown at 37oC, 5% CO2 and 95% air for 72h. Trypan blue was used to determine the cell viability and proliferation. Untreated and rapamycin-treated MCF-7 cells were also examined for morphological changes with an inverted-phase contrast microscope. Alteration in cell morphology was ascertained, along with a stage in the cell cycle and proliferation. In addition, cytotoxicity testing was performed using normal mouse breast mammary pads. Our results clearly showed that rapamycin exhibited inhibitory activity on MCF-7 cell lines. The IC50 value of rapamycin on the MCF-7 cells was determined as 0.4μg/ml (p<0.05). Direct observation by inverted microscopy demonstrated that the MCF-7 cells treated with rapamycin showed characteristic features of apoptosis including cell shrinkage, vascularization and autophagy. Cells underwent early apoptosis up to 24% after 72h. Analysis of the cell cycle showed an increase in the G0G1 phase cell population and a corresponding decrease in the S and G2M phase populations, from 81.5% to 91.3% and 17.3% to 7.9%, respectively. This study demonstrated that rapamycin may potentially act as an anti-cancer agent via the inhibition of growth with some morphological changes of the MCF-7 cancer cells, arrest cell cycle progression at G0/G1 phase and induction of apoptosis in late stage of apoptosis. Further studies are needed to further characterize the mode of action of rapamycin as an anti-cancer agent.